2016
DOI: 10.1039/c5an02018b
|View full text |Cite
|
Sign up to set email alerts
|

Does size matter? Study of performance of pseudo-ELISAs based on molecularly imprinted polymer nanoparticles prepared for analytes of different sizes

Abstract: Abstract. The aim of this work is to evaluate whether the size of the analyte used as template for the synthesis of molecularly imprinted polymer nanoparticles (nanoMIPs) can affect their performance in pseudo-enzyme linked immunosorbent assays (pseudo-ELISAs). Successful demonstration of a nanoMIPs-based pseudo-ELISA for vancomycin (1449.3 g mol -1 ) was demonstrated earlier. In the present investigation, the following analytes were selected: horseradish peroxidase (HRP, 44 kDa), cytochrome C (Cyt C, 12 kDa) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 25 publications
(42 reference statements)
0
29
0
Order By: Relevance
“…7,8 In addition, they can be considered as replacement for antibodies and have been used for the detection of several targets in ELISA-type assays. [9][10][11][12][13] The use of synthetic antibodies has a number of distinct advantages over their natural counterparts, including their cost-effectiveness, simple and scalable synthesis, and that no animals are required for the production process. 14,15 Due to their robust nature, nanoMIPs can be employed in harsh chemical environments such as extremes of pH, temperature and also in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In addition, they can be considered as replacement for antibodies and have been used for the detection of several targets in ELISA-type assays. [9][10][11][12][13] The use of synthetic antibodies has a number of distinct advantages over their natural counterparts, including their cost-effectiveness, simple and scalable synthesis, and that no animals are required for the production process. 14,15 Due to their robust nature, nanoMIPs can be employed in harsh chemical environments such as extremes of pH, temperature and also in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticles are isolated as an aqueous suspension which can be used as a direct replacement for antibodies. In a parallel study, the effect of the size (molar mass) of the templates used for imprinting in aqueous media was investigated16. It was found that nanoparticles prepared in this manner could be used in the biomimetic ELISA format to create effective assays for horseradish peroxidase (44 kDa), cytochrome C (12 kDa) and biotin (244.31 g mol −1 ) as well as vancomycin (1449.3 g mol −1 )7, however for the smallest template studied (melamine, 126.12 g mol −1 ), aqueous-based imprinting was not effective.…”
Section: Resultsmentioning
confidence: 99%
“…High affinity material is produced by virtue of an in-built affinity separation step, the template may be re-used, and the surface chemistry can be modified chemically without affecting the recognition properties of the MIPs56. The resultant particles are suitable for applications where antibodies are traditionally used, including sensors22232425 and assays71626. Imprinted nanoparticles have also been shown to selectively detect mammalian cell types by their expression of antigens2728.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NanoMIPs produced using a solid phase has been pioneered by our group 9 , 17 , 18 and the solid phase synthesis approach demonstrates superior advantages over the other MIP synthesis methods 17 21 : Low affinity polymers can be discarded during the manufacturing process by applying cold wash (1), high affinity nanoMIPs are collected by performing elution steps at high temperature (2), the template free receptors are obtained with this method, because nanoMIPs are removed from the template molecule rather than the template being removed from the MIP (3), the stability and size of the nanoMIPs are high owing to the selective washing and elution steps (4), a significant amount of MIPs can be obtained per synthesis that is adequate for long term experiments (5) 17 21 . These superior features have resulted in the successful applications of nanoMIPs in various fields such as pharmaceutical monitoring 9 , 13 , virus quantification 18 , 21 , endotoxin detection 22 , 23 , development of enzyme linked immonosorbent assays (ELISA) 24 , 25 , manufacturing of bioselective membrane filters 11 , and in vivo recognition of biomarkers 26 .…”
Section: Introductionmentioning
confidence: 99%